PENGEMBANGAN MEDIA PEMBELAJARAN FLASHCARD GUNA MENUNJANG PROSES PEMBELAJARAN MODEL MAKE A MATCH UNTUK MENDUKUNG KEMAMPUAN PEMECAHAN MASALAH PESERTA DIDIK - Widahyanti Widahyanti; Anita Dewi Utami; Widahyanti Widahyanti (Universitas Negeri Malang, 2024)
Abstract: Learning media has not been fully used in the learning process. In fact, learningmedia is an important component that can be used to help the learning processbecome more enjoyable, effective and efficient so that meaningful learning occurs.The development of learning media is very necessary to be able to support alearning process and support students' abilities. The aim of the research is todevelop flashcard learning media to support the make a match model learningprocess to support students' problem solving abilities. The method in this researchis research and development (Research & Development) referring to the ADDIEmodel which consists of analysis, design and development. The research subjectwas flashcard learning media in the make a match learning model in mathematicsmaterial and the test subjects were teachers and students at SMP Negeri 9 Malang.Based on the results of the data analysis obtained, it was concluded that theflashcard learning media that had been developed had a very valid category interms of the percentage of media suitability of 92.5%, validation of the material wasincluded in the very valid category with a percentage of 95%. Interviews conductedwith students also showed that students became more active, helpful andenthusiastic and supported students' problem solving abilities when flashcardmedia was used in the make a match type cooperative learning model